Applications of the analytic hierarchy process in management - Islam, Rafikul (2017)
Over the last three decades, managers, researchers, practitioners, management consultants and many other people have used the Analytic Hierarchy Process (AHP) to make decisions or to prioritize a set of factors in many areas of management. Perhaps, the most appealing reason for the method’s widespread use is its simplicity in application. Further, AHP can deal with subjective factors in decision making in a logical way. Number of real world applications of AHP is simply numerous. In this talk, only the following selected applications of AHP will be presented: Human Resource Management: - Developing A Human Resource Management Effectiveness Model - Selecting Managers for State-Owned Companies - Selection of Research Officers in the Saudi-Arabian Ministry of Foreign Affairs Total Quality Management: - Whether or Not to Implement ISO 9000 Quality Management System - Improving Service Quality at Restaurants - Selecting a Manufacturing Process for Benchmarking Environmental Management - Identifying Public Preferences for Land Preservation - Prioritizing Attributes in Urban Open Space Design - Prioritizing Factors in SWOT Analysis for a Finish Forestry Firm